(untitled) (Bangladesh Journal of Medical Science, 2025)
The effects of glucagon-like peptide-1 (GLP-1) receptor agonists on cardiovascular outcomes and body weight have garnered considerable clinical attention, especially in the context of addressing type 2 diabetes (T2D) and its related comorbidities. The purpose of this systematic review was to assess the safety and effectiveness of several GLP-1 receptor agonists in relation to weight loss and cardiovascular outcomes. Using a combination of keywords, MeSH terms, and Boolean operators, the search process was carried out in PubMed, Embase, Scopus, Web of Science, Cochrane Library, and ClinicalTrials.gov. The GRADE (Grading of Recommendations, Assessment, Development, and Evaluation) method was used to gauge the degree of certainty in the evidence, and the Cochrane’s RoB 2.0 tool was used to assess the risk of bias in the included studies. To reduce bias and mistakes, each paper was examined independently by two reviewers. The review comprised 21 studies in total. Weight, BMI, WC, SBP, TC, and TG were all considerably decreased by ligarglutide 3.0 mg in both obese/overweight people without T2D and those who had the disease. In a variety of groups, semaglutide 2.4 mg showed strong effectiveness in lowering weight, BMI, WC, SBP, and improving TG ratios. When paired with rigorous behavioural therapy, additional advantages were seen. Weight and metabolic indices were reduced in a dosedependent manner by tirzepatide. Liraglutide, semaglutide, albiglutide, dulaglutide, and efpeglenatide showed significant reductions in major adverse cardiovascular events, according to cardiovascular outcome-focused trials; lixisenatide and exenatide did not demonstrate significant cardiovascular benefits. Comparative investigations showed that exenatide QWS-AI provided better glycaemic control, while liraglutide and combination therapy significantly improved MetS-Z and android fat percentage. GLP-1 receptor agonists have often shown to have a major positive impact on improving metabolism, lowering cardiovascular risk, and losing weight. Behavioural treatments, the presence of T2D, and the particular GLP-1 agonist utilised all had an impact on the efficacy. These results provide credence to the use of GLP-1 receptor agonists as a helpful therapeutic option for patients with T2D and obesity who wish to manage their weight and cardiovascular health. BJMS, Volume: 24. Supplementary Issue 2025, Page : 45-58